2021
DOI: 10.35808/ersj/2174
|View full text |Cite
|
Sign up to set email alerts
|

Green Marketing: The Effectiveness of Socio-Demographic Variables for Explaining Green Purchases Behavior in Emerging Markets

Abstract: Purpose: This paper aimed to investigate how socio-demographic factors have the power to influence the purchase of green products. The differences between gender, age, education level, and personal financial situation were examined. Design/Methodology/Approach: We surveyed 650 Polish consumers. The sample displays the following socio-demographic characteristics: gender, age, education, place of residence, and financial situation. The research was carried out between 7 December 2018 and 7 January 2019. A seven-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…They also found that young consumers were sceptical about green products. They concluded that Polish consumers have insufficient knowledge about green products, affecting their purchasing behaviour [27].…”
Section: Purchase Behaviourmentioning
confidence: 99%
“…They also found that young consumers were sceptical about green products. They concluded that Polish consumers have insufficient knowledge about green products, affecting their purchasing behaviour [27].…”
Section: Purchase Behaviourmentioning
confidence: 99%